13q12.2 deletions in acute lymphoblastic leukemia lead to upregulation of FLT3 through enhancer hijacking - Yang, Minjun; Safavi, Setareh; Woodward, Eleanor L; Duployez, Nicolas; Olsson-Arvidsson, Linda; Ungerbäck, Jonas; Sigvardsson, Mikael; Zaliova, Marketa; Zuna, Jan; Fioretos, Thoas; Johansson, Bertil; Nord, Karolin H; et al. (Blood, 2020)
Mutations in the FMS-like tyrosine kinase 3 (FLT3) gene in 13q12.2 are among the most common driver events in acute leukemia, leading to increased cell proliferation and survival through activation of the phosphatidylinositol 3-kinase/AKT-, RAS/MAPK-, and STAT5-signaling pathways. In this study, we examine the pathogenetic impact of somatic hemizygous 13q12.2 microdeletions in B-cell precursor (BCP) acute lymphoblastic leukemia (ALL) using 5 different patient cohorts (in total including 1418 cases). The 13q12.2 deletions occur immediately 5' of FLT3 and involve the PAN3 locus. By detailed analysis of the 13q12.2 segment, we show that the deletions lead to loss of a topologically associating domain border and an enhancer of FLT3. This results in increased cis interactions between the FLT3 promoter and another enhancer located distally to the deletion breakpoints, with subsequent allele-specific upregulation of FLT3 expression, expected to lead to ligand-independent activation of the receptor and downstream signaling. The 13q12.2 deletions are highly enriched in the high-hyperdiploid BCP ALL subtype (frequency 3.9% vs 0.5% in other BCP ALL) and in cases that subsequently relapsed. Taken together, our study describes a novel mechanism of FLT3 involvement in leukemogenesis by upregulation via chromatin remodeling and enhancer hijacking. These data further emphasize the role of FLT3 as a driver gene in BCP ALL.
Keywords: sekvenování celého genomu; Chromosome Disorders; Gene Expression Regulation, Leukemic; Cell Line; chromozomální delece; kohortové studie; mikročipová analýza; DNA Copy Number Variations; Up-Regulation; Cohort Studies; chromozomální poruchy; restrukturace chromatinu; upregulace; jednonukleotidový polymorfismus; variabilita počtu kopií segmentů DNA; sekvenování transkriptomu; regulace genové exprese u leukemie; lidské chromozomy, pár 13; akutní lymfatická leukemie; zesilovače transkripce; tyrosinkinasa 3 podobná fms; Polymorphism, Single Nucleotide; lidé; Enhancer Elements, Genetic; Humans; Microarray Analysis; buněčné linie; fms-Like Tyrosine Kinase 3; Chromosomes, Human, Pair 13; Precursor Cell Lymphoblastic Leukemia-Lymphoma; RNA-Seq; Chromosome Deletion; Chromatin Assembly and Disassembly; Whole Genome Sequencing